Effect of fasting on short‐term visual plasticity in adult humans. (9th December 2022) - Animali, Silvia; Steinwurzel, Cecilia; Dardano, Angela; Sancho‐Bornez, Veronica; Del Prato, Stefano; Morrone, Maria Concetta; Daniele, Giuseppe; Binda, Paola
Abstract: Brain plasticity and function is impaired in conditions of metabolic dysregulation, such as obesity. Less is known on whether brain function is also affected by transient and physiological metabolic changes, such as the alternation between fasting and fed state. Here we asked whether these changes affect the transient shift of ocular dominance that follows short‐term monocular deprivation, a form of homeostatic plasticity. We further asked whether variations in three of the main metabolic and hormonal pathways affected in obesity (glucose metabolism, leptin signalling and fatty acid metabolism) correlate with plasticity changes. We measured the effects of 2 h monocular deprivation in three conditions: post‐absorptive state (fasting), after ingestion of a standardised meal and during infusion of glucagon‐like peptide‐1 (GLP‐1), an incretin physiologically released upon meal ingestion that plays a key role in glucose metabolism. We found that short‐term plasticity was less manifest in fasting than in fed state, whereas GLP‐1 infusion did not elicit reliable changes compared to fasting. Although we confirmed a positive association between plasticity and supraphysiological GLP‐1 levels, achieved by GLP‐1 infusion, we found that none of the parameters linked to glucose metabolism could predict the plasticity reduction in the fasting versus fed state. Instead, this was selectively associated with the increase in plasma beta‐hydroxybutyrate (B‐OH) levels during fasting, which suggests a link between neural function and energy substrates alternative to glucose. These results reveal a previously unexplored link between homeostatic brain plasticity and the physiological changes associated with the daily fast‐fed cycle. Abstract : Skipping breakfast impairs short‐term ocular dominance plasticity in adult healthy humans. Replacing a standardised meal with a GLP‐1 infusion does not rescue this plasticity impairment. The plasticity impairment during fasting parallels the enhancement of fatty acids metabolism.